Determination of unsaturated hydraulic conductivity and sorptivity of a soil using a disk permeameter - Borges, Edvane; Antonino, Antonio Celso Dantas; Olio, Attilio Dall; Audry, Pierre; Carneiro, Clemente José Gusmão (Pesquisa Agropecuaria Brasileira, 1999)
Sorptivity and hydraulic conductivity were determined by two methods using disc permeameters. Infiltration experiments were carried out on three horizons of a representative soil of the semi-arid region, located in Santa Maria da Boa Vista, State of Pernambuco, Brazil. Water was supplied to this soil by disc permeameters at potentials of 0, -2.5, -5 and -10 cm of water. In the first method, hydraulic conductivity was measured using estimates of sorptivity and steady state fluxes. In the second, sorptivity and hydraulic conductivity were determined using measurements of steady state fluxes with two disc permeameters of different radius. Results of the second method, regarding characteristic times and characteristic pore radius, were more consistent than those of the first one. Sorptivity was as important as hydraulic conductivity to characterize the infiltration process. The abrupt reduction of the characteristic pore radius in the horizon A2/B with changes in the water supply potential indicates the structure heterogeneity of this horizon and allows the identification of the role of the clay compact volumes on the infiltration process.